Distribution of Marine Fungi and Fungus-Like Organisms in the South China Sea and Their Potential Use in Industry and Pharmaceutical Application - Gareth Jones, E.B.; Alias, Siti Aisyah; Pang, Ka-Lai (Malaysian Journal of Science, 2013)
In this article we document the distribution and ecology of marine fungi in the South China Sea. They have been widely studied in this area, resulting in approximately a third of all described marine fungi (560 species) reported from the South China Sea, and especially from Hong Kong, Malaysia, Thailand and Taiwan. Sixty-nine marine fungi have been described from countries bordering the South China Sea, mainly ascomycetes species, with many from Malaysia (25 species). Many of the fungi documented have been found on mangrove substrates, including attached and drift mangrove wood. This has resulted in detailed studies of their vertical and horizontal distribution in mangroves, and sequence of colonisation on submerged test blocks. Many marine fungi isolated from the South China Sea have been screened for new chemical structures with bioactivity. Foremost has been Professor Y. C. Lin and his colleagues at Guangzhou University who have described a wide range of chemical structures including 42 new or novel compounds and 35 known compounds from 25 fungal strains (comprising endophytes, obligate and marine-derived fungi). Although fi lamentous fungi have been widely collected in the South China Sea, information on chytrids, mucoraceous fungi and fungal-like organisms is meagre and warrants further investigation. (Keywords: distribution, ecology marine fungi, South China Sea, omega-3-fatty acids, bioactive compounds, industrial application).